2019
DOI: 10.1002/mdc3.12838
|View full text |Cite
|
Sign up to set email alerts
|

Questionable Dystonia in Essential Tremor Plus: A Video‐Based Assessment of 19 Patients

Abstract: View Supplementary Video 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 6 publications
3
24
0
Order By: Relevance
“…Using the Consensus Statement definition [ 1 ], a majority of our patients (72.1%, excluding ET-PD) were classified as ET plus. This is consistent with other recently published studies [ 9 10 18 ]. Similar to our prior report, involving 350 patients with ET [ 19 ], and other studies [ 20 ], the current series again demonstrated a bimodal age-at-onset distribution ( Figure 1 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Using the Consensus Statement definition [ 1 ], a majority of our patients (72.1%, excluding ET-PD) were classified as ET plus. This is consistent with other recently published studies [ 9 10 18 ]. Similar to our prior report, involving 350 patients with ET [ 19 ], and other studies [ 20 ], the current series again demonstrated a bimodal age-at-onset distribution ( Figure 1 ).…”
Section: Discussionsupporting
confidence: 94%
“…The addition of "ET plus" as a diagnostic category in the Movement Disorder Society Consensus Statement [1] draws attention to these additional features. Since the publication, our and other studies [9][10][11]18] have found that most patients previously diagnosed as ET must be reclassified as ET plus. Furthermore, the additional, nontremor features suggest the possibility of etiopathogenic subtypes.…”
Section: Resultsmentioning
confidence: 99%
“…However, the ET patients were followed up in our outpatient clinic for a relatively long period, thus minimizing the risk of misdiagnosis. In this regard, all patients had bilateral postural and kinetic tremor of the upper limbs, whilst none had subtle dystonia signs or clinically detectable parkinsonian features [25,26]. All patients had discontinued all therapies at least 48 h before the experimental evaluation, therefore reducing the possibility that medications affected our kinematic measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ET can during the course of their illness develop signs of dystonia and parkinsonism, and some may even develop a secondary PD (22,23). This is generally a later phenomenon.…”
Section: Discussionmentioning
confidence: 99%